Active Shingles Infection as Detected on 18F-FDG PET/CT - Muzaffar, Razi; Fesler, Mark; Osman, Medhat M. (Frontiers in Oncology, 2013)
We present the case of a 56 year old male with a history of recurrent follicular lymphoma undergoing chemotherapy with multiple 18F-FDG PET-CT studies at an outside facility. He developed a painful erythematous, pruritic rash in the left back requiring a visit to the emergency room. He was diagnosed and treated for varicella zoster infection. He then presented to our imaging center 2 months later for a follow up 18F-FDG PET/CT study. Imaging demonstrated a cutaneous band of increased metabolic activity in the upper back following a dermatomal distribution. This was confirmed to be in the same area as the treated varicella zoster eruption. A subsequent follow up 18F-FDG PET-CT scan 4 months later to confirm tumor resolution demonstrated the abnormal band of uptake in the back had resolved. This case illustrates the significance of being aware of this entity and to distinguish it from metastasis, especially in patients with a known history of malignancy.